2004
DOI: 10.1016/j.cub.2004.06.058
|View full text |Cite
|
Sign up to set email alerts
|

The Hereditary Spastic Paraplegia Gene, spastin, Regulates Microtubule Stability to Modulate Synaptic Structure and Function

Abstract: Loss of Dspastin in Drosophila causes an aberrantly stabilized microtubule cytoskeleton in neurons and defects in synaptic growth and neurotransmission. These in vivo data strongly support previous reports, providing a probable cause for the neuronal dysfunction in spastin-linked HSP disease. The role of Spastin in regulating neuronal microtubule stability suggests therapeutic targets for HSP treatment and may provide insight into neurological disorders linked to microtubule dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
220
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 223 publications
(238 citation statements)
references
References 38 publications
9
220
3
2
Order By: Relevance
“…Previous studies have made strong inferences about altered microtubule dynamics in different genetic mutants and disease models based wholly on very indirect assays of the local microtubule state within synapses (Zhang et al, 2001;Huot et al, 2001;McDermott et al, 2003;Lu et al, 2004;Sherwood et al, 2004;Trotta et al, 2004;Zhang and Broadie, 2005;Orso et al, 2005). The goal of this study was to develop techniques to directly assay microtubule dynamics, locally at synapses, in living neurons in situ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have made strong inferences about altered microtubule dynamics in different genetic mutants and disease models based wholly on very indirect assays of the local microtubule state within synapses (Zhang et al, 2001;Huot et al, 2001;McDermott et al, 2003;Lu et al, 2004;Sherwood et al, 2004;Trotta et al, 2004;Zhang and Broadie, 2005;Orso et al, 2005). The goal of this study was to develop techniques to directly assay microtubule dynamics, locally at synapses, in living neurons in situ.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously proposed altered synaptic microtubule dynamics as a causative defect in Drosophila genetic models of Fragile X Syndrome (FXS) and Hereditary Spastic Paraplegia (HSP) (Zhang et al, 2001;Trotta et al, 2004;Zhang and Broadie 2005): FXS is caused by loss of function of the FMR1 gene, which encodes a negative translational regulator of Futsch/ microtubule associated protein 1B (MAP1B), and 40% of HSP cases are linked to mutations of the spastin gene, which encodes a microtubule severing protein. Indirect evidence suggests that synaptic microtubules are hyper-stabilized in both mutants, but several mechanisms could be responsible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has demonstrated that null mutations in the Drosophila spastin homolog recapitulate the motor defects associated with AD-HSP along with defects in synaptic structure and function. [25][26][27] Work presented at the conference by the Sherwood lab (Duke University, Durham, NC) focused on understanding Spas function through several genetic approaches in the fly. First they demonstrated that both wildtype fly and human Spas proteins rescue the null drosophila phenotypes showing the evolutionary conservation of protein function and further indicating the usefulness of this Drosophila model.…”
Section: Drosophila Neurological Disease Modelsmentioning
confidence: 99%